2002
DOI: 10.1037/0022-0167.49.4.484
|View full text |Cite
|
Sign up to set email alerts
|

Examining the generalizability of problem-solving appraisal in Black South Africans.

Abstract: Two studies examined the generalizability of the Problem Solving Inventory (PSI; P. P. Heppner, 1988) through research with Black South African samples. Study 1 examined the generalizability of the factor structure of the PSI through confirmatory factor analysis. Study 2 examined the relationship between problem solving and psychological distress and tested a Problem-Solving Confidence mediational model of psychological distress through structural equation modeling. The estimates of the factor structure as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
62
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(84 citation statements)
references
References 62 publications
(159 reference statements)
17
62
1
2
Order By: Relevance
“…It is recommended that the items of the scale be grouped into parcels or bundles so as to avoid having to estimate a large number of parameters (Russel, Kahn, Spoth, & Altmaier, 1998) and to reduce the possibility of distortion from idiosyncratic characteristics of individual items in fitting the model to the data (Heppner et al, 2002). It has been demonstrated that the creation of bundles allows for a distribution closer to normal (Takahashi & Nasser, 1996) and it has also been empirically shown that the structural parameters (i.e., path coefficients) for bundled and individual items were largely the same (Russel et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…It is recommended that the items of the scale be grouped into parcels or bundles so as to avoid having to estimate a large number of parameters (Russel, Kahn, Spoth, & Altmaier, 1998) and to reduce the possibility of distortion from idiosyncratic characteristics of individual items in fitting the model to the data (Heppner et al, 2002). It has been demonstrated that the creation of bundles allows for a distribution closer to normal (Takahashi & Nasser, 1996) and it has also been empirically shown that the structural parameters (i.e., path coefficients) for bundled and individual items were largely the same (Russel et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…However, existing studies on coping with life difficulties are very contradictory. Literature analysis of relevant concepts and related measures revealed two major trends in this research area: coping with stress (Lazarus and Folkman, 1984; Carver and Scheier, 1994) and applied problem solving (Heppner and Petersen, 1982; D’Zurilla and Nezu, 1990; Heppner et al, 2002, 2004). The most known in the first designated area of research is a cognitive theory of stress, developed by Lazarus and Folkman (1984), that interprets coping as either problem- or emotion-oriented.…”
Section: Introductionmentioning
confidence: 99%
“…[6,7] Problem çözme becerileri, kişisel ve mesleki yaşamda karşılaşılan sorunlarla daha etkin baş etmeyi ve uyumu desteklemektedir. [8][9][10][11] Günümüzde bilgi teknolojilerinin başlıca kaynağı olan İnternet; her türlü bilgiye hızlı, kolay, ucuz ve güvenilir erişimi, kişilerarası iletişimi ve bilgi paylaşımını sağlayarak yaşamı kolaylaştırmaktadır. [2,3,12] İnternet kullanımına yönelik tutum; bireyin bu teknolojiyle ilgili duygu, düşünce ve davranışlarını etkileyen, kaynağını bilgisayar objesine ilişkin inançlar, deneyimler ve değer yargılarından alan zihinsel süreçlerdir.…”
Section: Introductionunclassified